Absorption troughs of Lyα emitters in HETDEX - Weiss, Laurel; Davis, Dustin; Gebhardt, Karl; Gazagnes, Simon; Khanlari, Mahan Mirza; Cooper, Erin Mentuch; Chisholm, John; Berg, Danielle; Bowman, William P.; Byrohl, Chris; Ciardullo, Robin; Fabricius, Maximilian; et al. (The astrophysical journal, 2024)
The Hobby-Eberly Telescope Dark Energy Experiment (HETDEX) is designed to detect and measure the redshifts of more than 1 million Lyα emitting galaxies (LAEs) 1.88 < z < 3.52. In addition to its cosmological measurements, these data enable studies of Lyα spectral profiles and the underlying radiative transfer. Using the roughly half a million LAEs in the HETDEX Data Release 3, we stack various subsets to obtain the typical Lyα profile for the z ∼ 2-3 epoch and to understand their physical properties. We find clear absorption wings around Lyα emission, which extend ∼2000 km s−1 both redward and blueward of the central line. Using far-UV spectra of nearby (0.002 < z < 0.182) LAEs in the COS Legacy Archive Spectroscopic Survey treasury and optical/near-IR spectra of 2.8 < z < 6.7 LAEs in the Multi Unit Spectroscopic-Wide survey, we observe absorption profiles in both redshift regimes. Dividing the sample by volume density shows that the troughs increase in higher-density regions. This trend suggests that the depth of the absorption is dependent on the local density of objects near the LAE, a geometry that is similar to damped Lyα systems. Simple simulations of Lyα radiative transfer can produce similar troughs due to absorption of light from background sources by H i gas surrounding the LAEs.